ICU shift related effects on sleep, fatigue and alertness levels. (24th January 2020) - Bihari, S; Venkatapathy, A; Prakash, S; Everest, E; McEvoy R, D; Bersten, A
Abstract: Background: Shift work may lead to suboptimal sleep resulting in impaired alertness, and lowered performance levels, all of which can lead to medical errors. Aims: To examine fatigue, sleepiness and behavioural alertness prospectively in a tertiary level Australian intensive care unit (ICU). Methods: All full-time doctors providing 24-h resident cover on a 12-h day and 12-h night shift roster were invited to participate in this study. Data collected included Epworth Sleepiness Scale (ESS), sleep and awake history, Samn-Perelli Fatigue (SPF) Scale, Karolinska Sleepiness Scale (KSS) and iOS-based Psychomotor Vigilance Test (behavioural alertness). Data about medical emergency team (MET) shifts were collected separately as they were perceived to be busier shifts. Results: Twenty-nine ICU doctors participated in this study for a consecutive 6-week period. At baseline the median (interquartile range (IQR)) ESS was 5 (3–9). Day shift leads to an increase in fatigue and sleepiness (both P < 0.01). Night shift leads to worsening in fatigue, sleepiness and psychomotor vigilance (all P < 0.01). MET shifts had a lower psychomotor vigilance than non-MET shifts. The difference in the psychomotor vigilance was mostly due to the difference in recorded lapses and response time. Conclusions: Shift work ICU doctors experience high levels of fatigue and sleepiness. Night shifts also lead to decreased vigilance. This is even more evident in doctors working MET shifts. These factors may lead to errors. Optimal rostering may reduce these effects and improve patient safety.